2015
DOI: 10.1016/j.biomaterials.2015.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV-photofunctionalization on oral bacterial attachment and biofilm formation to titanium implant material

Abstract: Bacterial biofilm infections remain prevalent reasons for implant failure. Dental implant placement occurs in the oral environment, which harbors a plethora of biofilm-forming bacteria. Due to its trans-mucosal placement, part of the implant structure is exposed to oral cavity and there is no effective measure to prevent bacterial attachment to implant materials. Here, we demonstrated that UV treatment of titanium immediately prior to use (photofunctionalization) affects the ability of human polymicrobial oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
105
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 65 publications
(74 reference statements)
4
105
0
2
Order By: Relevance
“…During this period, bacteria can colonize the implant site and initiate the formation of biofilms, which are more resistant to host immunity than planktonic cells. 17 In this study, UV treatment inhibited biofilm formation by A. oris, even after 6 hours of exposure to a high bacterial load (.2×10 8 cfu/mL). Therefore, this …”
mentioning
confidence: 51%
See 1 more Smart Citation
“…During this period, bacteria can colonize the implant site and initiate the formation of biofilms, which are more resistant to host immunity than planktonic cells. 17 In this study, UV treatment inhibited biofilm formation by A. oris, even after 6 hours of exposure to a high bacterial load (.2×10 8 cfu/mL). Therefore, this …”
mentioning
confidence: 51%
“…Currently, superhydrophilicity is rendered to titanium surfaces via a 12-minute UV treatment, preventing biofilm formation for up to 16 hours. 17 This short treatment time allows for the treatment of implants chair-side as well as for immediate insertion of treated implants onto the bone. Therefore, we hypothesized that UV treatment would yield reduced rates of postoperative infection and superior osteogenic activity for TNS.…”
mentioning
confidence: 99%
“…In an in vitro study under static and dynamic conditions, UVA illumination prior to bacterial colonization induced a reduction in adhesion rates and a significant decrease in the adhesion strength of S. epidermidis and S. aureus, without altering biocompatibility 132) . In a multispecies study authors found a positive effect on the attachment and biofilm formation of complex oral microbial communities to UV treated titanium 167) .…”
Section: Uv-activatable Surfacesmentioning
confidence: 99%
“…[1][2][3] Nevertheless, many reasons of implant failure are still associated with peri-implantitis 4 and appear to be resolved. On the implant surfaces, the adsorption of the subsequent accumulation of bacteria and biomolecular pellicles are the main stimuli for inducing peri-implantitis processes.…”
Section: Introductionmentioning
confidence: 99%
“…On the implant surfaces, the adsorption of the subsequent accumulation of bacteria and biomolecular pellicles are the main stimuli for inducing peri-implantitis processes. 4 Though the biocompatibility of Ti and its alloys has been recognized, 5 it remains difficult to carry out all the requirements, such as osseointergration, biocompatibility, mechanical properties and antibacterial ability. To achieve excellent implant biomaterials, the Ti and its alloys often need modifications, such as sandblasting processing, 6 acid treatment, 7 alkali treatment, 8 laser etching, 9 microarc oxidation 10 and anodic oxidation 11 and so on.…”
Section: Introductionmentioning
confidence: 99%